From Linkages to Disconnects: The Rapid Response Mechanism (RRM) under the United States-Mexico-Canada Agreement (USMCA) - Rioux, Michèle; L’Homme, Charles-Olivier (Revue Interventions économiques / Papers in Political Economy, 2026)
Labor provisions in the USMCA, and more specifically its RRM, offer a good case study for this special issue. As a tool for labor rights enforcement, it also is a strategic instrument to realign production away from low-cost production areas. The RRM represents a rare instance of an embedded “trade for” linkage, wherein trade policy is explicitly used as a tool to enforce labor rights. It embodies the kind of linkage that the special issue describes as the strongest form of trade integration, both substantively and procedurally, that ties a trade to social and other non-commercial objectives. However, this article reveals the fragility of trade linkages in a volatile political and strategic context. The re-election of Donald Trump endangers the future of the RRM and the broader social dimension of the USMCA. Trump’s America First doctrine and its deregulatory economic agenda suggest a more disembedded and strategically oriented trade policy. This potential rollback echoes the concept of “trade disconnects,” in which integrated social concerns are de-linked or marginalized when they conflict with nationalist, security-based, or purely commercial imperatives. Yet, the RRM remains an important trade policy instrument and is used by the new administration as a strategic tool to block “social dumping” in North America. This article has four sections: 1) the trade-labor linkage in the literature; 2) the USMCA’s RRM and how it improved the NAFTA side-agreement; 3) the RRM cases and their impacts; and 4) the future of the RRM. As the USMCA approaches its 2026 review, it is crucial to assess the RRM's effectiveness and its future trajectory.